Reducing PHYTOENE SYNTHASE activity fine-tunes the abundance of a cis-carotene-derived signal that regulates the PIF3/HY5 module and plastid biogenesis - Hou, Xin (Journal of experimental botany, 2024)
© The Author(s) 2023. Published by Oxford University Press on behalf of the Society for Experimental Biology. All rights reserved. For permissions, please email: journals.permissionsoup.com.